Bapalas as Alternative Dispute Resolution of Fighting on Muslim Dayak Community in Muara Teweh, Central Kalimantan - Helim, Abdul; Ahmad, Sabarudin; Padlianor, Padlianor (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2022)
This study discusses the tendency of the Muara Teweh Muslim Dayak community, who prefers bapalas in resolving fighting disputes over other legal remedies. Bapalas is a traditional dispute resolution of fights with the help of mantir and community leaders and is attended by the families of both parties. In the Dayak community, there are various bapalas, such as midwives bapalas, marriages bapalas, births bapalas, death bapalas, and fights bapalas. This research focuses on studying the fight bapalas as an alternative dispute resolution for fights in the community. Fighting is part of criminal law, usually resolved through litigation by repressive settlements. However, it is different in the Muslim Dayak community in Muara Teweh. They prefer to settle the dispute through this bapalas tradition. The research was conducted using empirical legal research methods using an Islamic law approach. The theory used is the theory of ‘urf and the concept of iṣlāḥ in Islam. The study result indicates that the Muslim Dayak community in Muara Teweh prefers this settlement because, first, it has become customary law that has been passed for generations. Second, bapalas minimize the grudges between the conflicting parties. Third, compared to other resolutions, primarily through litigation, bapalas are much easier dan more effective in resolving conflicts, especially in terms of time. This dispute resolution model aligns with Islamic law according to 'urf and the concept of Islam.‘Urf can be a source of law as long as it does not conflict with sharia and is in line with the sadd al-żarī‘ah method, which means if the customs in society can prevent or block the harm, then it is allowed. It is also in line with the concept of iṣlāḥ that bapalas is a conflict resolution method that can eliminate and stop hostility and conflict between humans.